1973
DOI: 10.1172/jci107203
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Effect of Prostaglandin E1 on Renal Water Excretion

Abstract: ABS TRA CT The present study examined the effect of prostaglandin El (PGE1) on renal water excretion in the anesthetized dog. Renal perfusion pressure was kept constant by adjustment of a suprarenal aortic clamp. In seven experiments the intravenous administration of PGE1 (7 /Lg/min) significantly increased urinary osmolality from 76 to 381 mosmol (P < 0.001) and decreased free water clearance from 2.2 to -0.02 ml/ min (P < 0.001). These effects promptly were reversed with cessation of the infusion. This antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
2

Year Published

1973
1973
1992
1992

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 17 publications
3
25
1
2
Order By: Relevance
“…Some authors (21) have suggested that catecholamines may directly suppress the release of vasopressin. While the results of recent investigations suggest that the effect of isoproterenol (17) and prostaglandin (22) on vasopressin release is mediated indirectly as a consequence of alterations in systemic hemodynamics, the present results do not exclude a direct central effect of norepinephrine on vasopressin release. Alternatively, however, the increase in systemic arterial pressure which occurred during the intravenous infusion of norepinephrine could have caused a suppression of vasopressin release or initiated a reflex which in turn led to a diminution in vasopressin release.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Some authors (21) have suggested that catecholamines may directly suppress the release of vasopressin. While the results of recent investigations suggest that the effect of isoproterenol (17) and prostaglandin (22) on vasopressin release is mediated indirectly as a consequence of alterations in systemic hemodynamics, the present results do not exclude a direct central effect of norepinephrine on vasopressin release. Alternatively, however, the increase in systemic arterial pressure which occurred during the intravenous infusion of norepinephrine could have caused a suppression of vasopressin release or initiated a reflex which in turn led to a diminution in vasopressin release.…”
Section: Resultscontrasting
confidence: 99%
“…METHODS 33 experiments were performed in 22 mongrel dogs of either sex weighing [20][21][22][23][24][25][26][27][28][29][30] kg. Food was withheld 18 h before study but water was allowed ad lib.…”
Section: Introductionmentioning
confidence: 99%
“…30 experiments were performed in 19 mongrel dogs of either sex weighing [20][21][22][23][24][25][26][27][28][29][30] kg. Food was withhetd from these animals for 18 h before study, but water was allowed ad lib.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that a sudden variation in blood pressure is probably the most important stimulus for vasopressin secretion. Infusion of PGE1 generally induces diuresis, but Berl and Schrier (28) reported that the intravenous administration of PGE1 in a high dose (7 /tg/min) produced an antidiuresis, and suggested that this antidiuresis was due to the release of ADH provoked by the systemic hemodynamic effects of the high intravenous dose of PGE1, because the antidiuretic effect of intravenous PGE1 was not observed in hypophysectomized dogs. The antidiuresis induced by the high intravenous dose of PGI2…”
Section: Discussionmentioning
confidence: 99%